Requirements, Implementation and Applications of Hand-held Virtual Reality - Hwang, Jane; Jung, Jaehoon; Yim, Sunghoon; Cheon, Jaeyoung; Lee, Sungkil; Choi, Seungmoon; Kim, Gerard J. (International Journal of Virtual Reality, 2006)
While hand-held computing devices are capable of rendering advanced 3D graphics and processing of multimedia data, they are not designed to provide and induce sufficient sense of immersion and presence for virtual reality. In this paper, we propose minimal requirements for realizing VR on a hand-held device. Furthermore, based on the proposed requirements, we have designed and implemented a low cost hand-held VR platform by adding multimodal sensors and display components to a hand-held PC. The platform enables a motion based interface, an essential part of realizing VR on a small hand-held device, and provides outputs in three modalities, visual, aural and tactile/haptic for a reasonable sensory experience. We showcase our platform and demonstrate the possibilities of hand-hand VR through three VR applications: a typical virtual walkthrough, a 3D multimedia contents browser, and a motion based racing game